2014
DOI: 10.1002/app.40449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a titanate coupling agent on the mechanical and thermo‐physical properties of talc‐reinforced polyethylene compounds

Abstract: An experimental study was carried out to investigate the effects of a titanate coupling agent on the mechanical properties, moisture absorption, and thermal conductivity of talc-filled high-density polyethylene (HDPE). Talc (0-35 wt %) was used as reinforcement particulate filler in an HDPE matrix and samples were prepared in a micro-compounder and an injection molding machine. Isopropyl tri(dioctyl)phosphate titanate (0.5 wt %) was used as coupling agent. Composites with and without coupling agent were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…They reported that filler treatment enhances the polymerfiller adhesion and accordingly improves mechanical properties. Other researchers 64) concluded that the addition of TCA to resultant composites increases the stiffness and tensile strength of composites. This result verifies that such an agent is effective at low filler concentrations.…”
Section: Ceramic Fillersmentioning
confidence: 99%
“…They reported that filler treatment enhances the polymerfiller adhesion and accordingly improves mechanical properties. Other researchers 64) concluded that the addition of TCA to resultant composites increases the stiffness and tensile strength of composites. This result verifies that such an agent is effective at low filler concentrations.…”
Section: Ceramic Fillersmentioning
confidence: 99%
“…The use of titanate coupling agents is preferred not only because of their bridge effect between the inorganic llers and the polymer matrix, [46][47][48][49] but also because of their suitability for a variety of inorganic llers, including llers having surface hydroxyl groups and llers such as carbonates and carbon black which can not be modied by silane coupling agents.…”
mentioning
confidence: 99%
“…In a high‐density polyethylene (HDPE) matrix containing carbon black, the addition of talc particles resulted in higher impact resistance, thermal conductivity, thermal diffusivity, and specific density, but only a marginal improvement was observed in tensile strength (approximately 7.5%) 9 . A subsequent study showed that the addition of a titanate coupling agent to the talc particles resulted in a better filler‐matrix adhesion, consequentially, it was observed an increase in tensile strength of up to 18% and of up to 82% in stiffness, in comparison to the virgin polymer 10 . However, the treated composites showed significantly lower ductility (average 28% decrease in elongation at break) when compared with the composites with untreated filler 10 .…”
Section: Introductionmentioning
confidence: 95%